2016
DOI: 10.1177/0020720916630325
|View full text |Cite
|
Sign up to set email alerts
|

Design of two experimental setups for programmable logic controller (PLC) laboratory

Abstract: As programmable logic controllers (PLC) technology, programming languages and communication capabilities have advanced, PLCs offer many control devices to be attached directly to the PLC. For this reason PLC education became an important issue in many interdisciplinary engineering departments of the Universities. In this paper an automation set for the laboratory of PLC is developed which can be operated in various ways by programming a PLC as desired. The designed set also enables the students to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As know that geometry of the Sun -Earth occurs some angles between the sun lights and the concerned surface of the Earth. In order to have maximum output solar power from the PV panel it is essential to know these angles [1,3,5,14,15,20]. For performance of PV systems at installation site, it is important to determine their optimum design.…”
Section: Basics Of the Solar Energymentioning
confidence: 99%
See 1 more Smart Citation
“…As know that geometry of the Sun -Earth occurs some angles between the sun lights and the concerned surface of the Earth. In order to have maximum output solar power from the PV panel it is essential to know these angles [1,3,5,14,15,20]. For performance of PV systems at installation site, it is important to determine their optimum design.…”
Section: Basics Of the Solar Energymentioning
confidence: 99%
“…To improve the efficiency, the solar panel should be such that it always receives maximum solar irradiance variability at ground level. Effective utilization of solar energy for a PV panel requires tracking of the sun [ 5,6,7]. If the PV system has a tracker unit, operators and/or installers would not need to make more corrections that include manual calculation cases at every second at interested location.…”
Section: Introductionmentioning
confidence: 99%
“…PLC is an integrated device with programming support that assigns inputs to the output after one or more operations such as logic, data processing, counting, database, arithmetic. PLCs can be used in sequential control, motion control, process control or data management.PLC architecture includes three conceptual layers: hardware, firmware and programmable area (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…5 Such projects provide students with experiments involving industrial hardware and software, as PLCs, sensors, Supervisory Control and Data Acquisition (SCADA) systems, and industrial communication networks for complementing the content addressed by theoretical disciplines, such as Automation, Control Systems Theory, Instrumentation and Measurement Systems, and Fieldbus Networks. 1,10,14,16…”
Section: Introductionmentioning
confidence: 99%
“…5 Such projects provide students with experiments involving industrial hardware and software, as PLCs, sensors, Supervisory Control and Data Acquisition (SCADA) systems, and industrial communication networks for complementing the content addressed by theoretical disciplines, such as Automation, Control Systems Theory, Instrumentation and Measurement Systems, and Fieldbus Networks. 1,10,14,16 Details of the industrial plant are shown in the "Didactic tool overview" section and Piping & Instrumentation Diagram (P&ID) is presented in Appendix 1. Basically, the plant consists of two reservoirs, two tanks, two water pumps, an electrical pump, a boiler, pipes and valves that connect these elements, four PLCs, two variable frequency drives, level sensors, and measurement equipment.…”
Section: Introductionmentioning
confidence: 99%